2022
DOI: 10.1371/journal.pone.0276558
|View full text |Cite
|
Sign up to set email alerts
|

Drinking and swimming around waterways: The role of alcohol, sensation-seeking, peer influence and risk in young people

Abstract: The role of individual and sociocultural factors contributing to drowning risk for young adults is complex and poorly understood. This study examined the relationship between behaviour in and around waterways and: 1) alcohol consumption; 2) resistance to peer influence; 3) sensation-seeking; 4) perception of risk among people aged 15–24 in Western Australia. A cross-sectional online survey was conducted at three time-points with a convenience sample. Predictor variables included: Alcohol Use Disorder Identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Previous research has shown that adolescents with high levels of sensation-seeking experience an increase in prefrontal and para-prefrontal dopamine secretion. This makes them more susceptible to novel, impulsive, and potentially risky impulses (Zhang et al, 2016(Zhang et al, , 2017 and are more likely to disregard the potential consequences of hazards (Leavy et al, 2022). Sensation-seeking predicts negative and positive risk-taking, whereas extroversion and openness are predominantly related to positive risk-taking (Patterson et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that adolescents with high levels of sensation-seeking experience an increase in prefrontal and para-prefrontal dopamine secretion. This makes them more susceptible to novel, impulsive, and potentially risky impulses (Zhang et al, 2016(Zhang et al, , 2017 and are more likely to disregard the potential consequences of hazards (Leavy et al, 2022). Sensation-seeking predicts negative and positive risk-taking, whereas extroversion and openness are predominantly related to positive risk-taking (Patterson et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The use of alcohol around water is influenced by the wider environment, including social norms [10], peer influence [2,6] and commercial determinants such as alcohol marketing [1]. One potential strategy may involve peer-focused interventions to target peer group norms, improve social negotiation skills [6] and encourage young adults to consider the disapproval of others [24]. However, interpersonal interventions, while necessary, may not be sufficient to combat the pervasive influence of the alcohol industry.…”
Section: Implications For Interventions To Reduce Alcohol Use Around ...mentioning
confidence: 99%
“…The studies were conducted in Australia (n = 11) [6,10,23,24,[30][31][32][33][34][35][36] or New Zealand (NZ; n = 2) [37,38], with two studies including participants from both Australia and the United Kingdom (UK) [32,33]. Eight studies were published in the last 5 years (since 2018) [6,10,[30][31][32][33][34][35].…”
Section: Prevalence and Risk Factors Of Alcohol Use By Young People I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Drowning prevention in adults is a complex, multifaceted public health issue [7,8]. Some risk factors (age, male 20,21]. In contrast, in LMICs, males are exposed daily to natural waterbodies as a source of livelihood, using water transport to and from work, including in vessels that are often overcrowded and poorly maintained [12,22,23].…”
Section: Introductionmentioning
confidence: 99%